2006
DOI: 10.1152/ajpheart.00817.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning enhances scavenging activity of reactive oxygen species and diminishes transmural difference of infarct size

Abstract: Reactive oxygen species (ROS) enhance myocardial ischemia-reperfusion (I/R) injury. Ischemic preconditioning (PC) provides potent cardioprotective effects in I/R. However, it has not been elucidated whether PC diminishes ROS stress in I/R and whether PC protects the myocardium from ROS stress transmurally and homogeneously. Isolated rabbit hearts perfused with Krebs-Henseleit buffer underwent 30 min of ischemia and 60 min of reperfusion. Hemodynamic changes and myocardial damage extent were analyzed in four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The thorax was opened and the heart was quickly removed. Hearts were retrogradely perfused using a Langendorff preparation (14) with Krebs-Henseleit solution, gassed with 95% O2 and 5% CO2 and paced at 200 beats/min. Left ventricular (LV) pressure, LV systolic pressure (LVSP), LV end diastolic pressure (LVEDP) and LV developed pressure (LVDP: the difference of LVSP and LVEDP) were continuously monitored using an intraventricular latex balloon connected to a transducer (AP-601G; Nihon Kohden Co., Tokyo, Japan).…”
Section: Isolated Rabbit Heart Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The thorax was opened and the heart was quickly removed. Hearts were retrogradely perfused using a Langendorff preparation (14) with Krebs-Henseleit solution, gassed with 95% O2 and 5% CO2 and paced at 200 beats/min. Left ventricular (LV) pressure, LV systolic pressure (LVSP), LV end diastolic pressure (LVEDP) and LV developed pressure (LVDP: the difference of LVSP and LVEDP) were continuously monitored using an intraventricular latex balloon connected to a transducer (AP-601G; Nihon Kohden Co., Tokyo, Japan).…”
Section: Isolated Rabbit Heart Preparationmentioning
confidence: 99%
“…Rabbits were assigned to 6 groups: the control group (n= 11) underwent 30 min global ischemia and 60 min reperfusion (30-60 min I/R); the H2O2 group (n= 11) underwent 30-60 min I/R with H2O2 infusion (50 μmol/l, 15 ml/min) just after reperfusion for 1 min with a syringe pump (syringe infusion pump 22; Harvard Apparatus Inc., Millis, USA) in order to enhance oxidative stress during the initial phase of the reperfusion period. The dose of H2O2 was determined by preliminary experiments in which infusions of 10 to 100 μmol/l H2O2 were tested (14). We found that 50 μmol/l H2O2 infusion causes a modifiable enhancement of LV dysfunction, i.e., approximately 40% reduction in LVDP after 60 min of reperfusion.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 3 more Smart Citations